CURRENT EVIDENCE ON BIOINFORMATICS ROLE AND DIGITAL FORENSICS THAT CONTRIBUTE TO FORENSIC SCIENCE: UPCOMING THREAT - Al Hakim, Rosyid; Putri, Esa; Hidayah, Hexa; Pangestu, Agung; Riani, Sri (Lembaga Pengembangan Kinerja Dosen, 2022)
Forensics has become an essential part of the disclosure of criminal evidence. A bioinformatics approach in the form of DNA forensics and digital forensics can be a good combination in disclosing digital-based criminal evidence. This study explains how the role of bioinformatics through the digital approach can be a means of forming new approaches in integration with digital forensics, called cyber-bioinformatics. Despite many hopes and challenges ahead, it does not rule out the possibility of criminal cases related to the privacy of human genomic data, so it proposes a new hypothesis, “cyber-bioinformatics.” The role of cyber-bioinformatics is very central in this regard.